2020
DOI: 10.1007/s10068-020-00768-w
|View full text |Cite
|
Sign up to set email alerts
|

Starch nanoparticles prepared by enzymatic hydrolysis and self-assembly of short-chain glucans

Abstract: Enzymatic hydrolysis and self-assembly are considered promising methods for preparation of starch nanoparticles (SNPs) because they are environmentally friendly, and time- and cost-effective. These methods are based on the self-assembly of short-chain glucans released from the α-1,6 bonds in amylopectin. Since their discovery, many studies have described the structural and physicochemical properties of self-assembled SNPs. Self-assembled SNPs can be prepared by two methods: using only the soluble portion conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 91 publications
(192 reference statements)
1
10
0
Order By: Relevance
“…Starchbased nanoparticles display unique properties, such as controllable release, improved water solubility, bioavailability, and improved delivery of active ingredients in foods and within the human body [111,112]. In addition to enhancing the properties of starch films, starch-based nanoparticles can be used to produce high value-added products, such as the biodegradable carriers for drug delivery [113].…”
Section: Value-added Products From Sweet Potato Starchmentioning
confidence: 99%
“…Starchbased nanoparticles display unique properties, such as controllable release, improved water solubility, bioavailability, and improved delivery of active ingredients in foods and within the human body [111,112]. In addition to enhancing the properties of starch films, starch-based nanoparticles can be used to produce high value-added products, such as the biodegradable carriers for drug delivery [113].…”
Section: Value-added Products From Sweet Potato Starchmentioning
confidence: 99%
“…17 GMPs formed by glucan selfassembly are affected by the individual physical properties of glucan with varying DPs. 18 Although ASs are present in various microorganisms, it has been shown that the enzyme properties are different depending on the microorganism in which they reside. 19 NpAS (AS of Neisseria polysaccharea) can synthesize glucans with higher DPs than those synthesized from DgAS; however, they have low specific activity and thermostability.…”
Section: Introductionmentioning
confidence: 99%
“…The process of nanoparticle production can be carried out according to two basic principles: “top-down” and “bottom-up” [ 28 ], which are carried out by the main groups of methods such as chemical (acid and/or enzymatic hydrolysis or their combination, renewal/micro perception) and physical methods (grinding, high-pressure homogenization, electrospray, gamma irradiation, and ultrasonic treatment) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The basis of the “top-down” method of producing nanoparticles is the destruction of bulk material to obtain nanoparticles, and the “bottom-up” method is carried out through the growth-up and aggregation of molecules [ 28 ]. The most widely implemented method for preparation of starch nanoparticles (“top-down”) involves acid hydrolysis, which makes it possible to remove more reactive amorphous regions from the supramolecular structure [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation